Integrated traditional Chinese and western medicine nursing of pressure injuries in a patient with stroke (1例中风后患者压力性损伤的中西医结合护理体会) - ZHANG Shiyu (张诗语); YANG Yu (杨宇); WU Mingjie (吴铭杰); LI Mengru (李梦儒); ZHANG Chen (张晨); HU Shirong (胡世荣) (Association of Integrative Nursing, 2023)
This paper summarized the integrated traditional Chinese and western medicine nursing of pressure injuries in a patient with stroke. Based on the principles of wound bed preparation, wound management combined with traditional Chinese medicine interventions by syndrome differentiation were carried out. Moxibustion, Chinese herbal medicine collapse stains and other techniques were performed to improve the wound healing and relieve the pain. (本文总结了1例中风后患者压力性损伤的中西医结合护理体会。基于伤口处理TIME原则处置创面, 同时中医辨证, 采取艾条悬灸、中药塌渍改善局部气血运行, 促进创面愈合, 减轻患者疼痛。)